Mental accounting in the context of savings and credit decisions. Evidence from Poland - Swacha-Lech, Magdalena; Solarz, Małgorzata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The main objective of this article is to identify and analyze the factors favouring the attitude of mental accounting in a wider sense. The analysis also helped identify the advantages and disadvantages resulting from the adoption of such an attitude as well as an assessment of the decisions made from the economic and psychological perspective. The following hypothesis was formulated: individuals characterised by debt aversion do not show an inclination to adopt the attitude of mental accounting in a wider sense. The core research method used in the study is logistic regression. The necessary empirical data of quantitative and qualitative nature were collected through surveys carried out in January 2013 through Computer Assisted Web Interview on a sample of 1000 Poles aged 15 or above. Other methods applied include a review and critical analysis of the subject literature. The study shows that among the factors identified, the strongest determinants of the mental accounting attitude are: having debt, having savings, debt aversion and the amount of monthly net income achieved. Both having debt and high monthly net income increase the likelihood of adoption of the attitudes of mental accounting, while the other factors have the opposite effect. In addition to the above factors, the behaviour of the people likely to do mental accounting is also affected by the objective of consumer spending as well as the time and the purpose of saving. Adopting the mental accounting attitude has some advantages, the most important of which is the fact that the attitude builds the ability to systematically manage the household budget and facilitates the efficient planning of income and expenditure as well as consistently sticking to previous decisions. Creating mental accounts helps organize personal finance and thus promotes achieving the goals of saving; this means that the psychological need of safety is met. With regard to the disadvantages of adopting the said attitude, it should be emphasized that the decision to protect savings, which results in the need for borrowing, exposes the individual to the risks of debt servicing and extra costs, which in extreme cases may bring about an over-indebtedness
Argumenta Oeconomica, 2019, Nr 2 (43), s. 351-384
Keywords: mental accounting; non-fungibility; financial decisions; logistic regression